Knowing the ropes: autonomy in the everyday life of Egyptian married women - Bashier, Neveen (AUC Knowledge Fountain, 2010)
The rationale behind this thesis has been to construct different frames of married women's autonomy in Egypt. Such frames are meant to describe different patterns of behavior in the everyday life of Egyptian married women. In order to construct such frames, a research has been conducted and twenty five in-depth interviews alongside a discussion group with five participants were held with self identified Egyptian married women. The research sought answers to questions on married women's definition of autonomy, how it is expressed in the various roles they play in their everyday lives, the constraints facing such autonomy in married women's view, and how their sense of autonomy may affect the gender identity of their children. This thesis employs feminist post-structuralist theory, the gender difference discourse, a feminist discursive approach on the development of gender identity, the theory of cognitive dissonance, and the concept of individual agency. This thesis also draws on studies conducted on gender-role attitudes among Egyptian adolescents, women's reaction to their domestication in the U.S.A, and married women's levels and indicators of autonomy in Egypt. Having been founded on the premise that women's situation in Egypt is greatly influenced by how they conceptualize their autonomy and their role in the family, this thesis deconstructs the notion of married women's autonomy to reconstruct it into five frames that illustrate women's different behaviors in the family. The five frames of autonomy coined in this thesis are: Subordination by Consent, Restrained Autonomy, Disguised Autonomy, Progressive Autonomy and Radical Autonomy. These frames constitute the contribution of this thesis to the study of women in Egypt.